Perbedaan Kemandirian Anak Ditinjau dari Pola Pengasuhan Orang Tua dengan Kakek Nenek pada Anak Usia Dini 3 Sampai 6 Tahun - Johan, Ales; Daeli, Weslei (Journal of Nursing Education and Practice, 2023)
Introduction: Early age is the age of children who are in the age range from 0 to 6 years. This early age is the age when children experience very rapid growth. Early age is often referred to as the golden age. At this time adults need to provide a good stimulus for children and provide useful skills for the child's future. This period is also the time for children to lay the first foundation in developing physical, cognitive, language, social-emotional abilities, self-concept, discipline, independence, art, morals, and religious values. Objectives: To find out whether there is a difference between children raised by parents and children raised by grandparents at RA. Persis Qurrata A'yun Depok kindergarten. Method: This study uses a descriptive method with a quantitative approach. The population in this study was all 57 RA. Persis Qurrata A'yun Depok kindergarten students. The sample used was 40 respondents aged 3 years to 6 years, 20 were raised by their parents and 20 were raised by their grandparents, while 17 other children were 7 people. Children not willing to be respondents, 4 children not being cared for by parents or grandparents, 5 children aged more than 6 years 2 children not coming during the study. Data collection using DDST (Denver Developmental Screening Test) and questionnaires. Results were analyzed using descriptive statistical tests. Result: The mean value of parental care is higher, 67.45 > 54.00, compared to the lower mean value of parental care. H0 is rejected and Ha is accepted, as seen from the calculation of the mean value. Conclusion: There is a difference in the independence of children who are cared for by parents and children who are cared for by grandparents.